Monepantel effectiveness against Haemonchus contortus and Trichostrongylus spp. with multiple resistance (ivermectin and febendazole) in goats (FAVE Sección Ciencias Veterinarias, 2016)
Monepantel is a new anthelmintic registered in Argentina exclusively for control of gastrointestinal nematodes of sheep and mostly directed toward controlling resistant parasites to current available classes of anthelmintics. The same nematodes also parasitize goats but pathophysiology and response are different in these hosts resulting in more severe parasitism and complexity in handling anthelmintic resistance. This report assess the efficacy of monepantel in goats maintained under field conditions and naturally parasitized by most common gastrointestinal nematodes from central Argentina (Haemonchus and Trichostrongylus) carrying alleles of multiple resistance (ivermectin and febendazole). According to the egg count reduction test, efficacies of 99% to 100% were observed after monepantel treatment at 3.75  mg/kg orally (1.5 ovine dose).
Keywords: antihelminthic resistance; goats; monepatel; Argentina